Optical and conductivity studies of polyvinyl alcohol-MXene (PVA-MXene) nanocomposite thin films for electronic applications - K. H., Tan; L., Samylingam; Aslfattahi, Navid; R., Saidur; K., Kadirgama (Elsevier Ltd, 2021)
A new family of 2D materials known as MXenes (Ti3C2Tx) is combined with polyvinyl alcohol (PVA) to form nanocomposites thin film with a thickness in micrometre range (7.20–7.88 µm) by using a relatively simple way, a drop-casting technique. The multi-layered structure of the MXenes bound together with PVA results in a high degree of structural disorder due to increasing defects in the nanocomposites. Detailed optical studies include UV–Vis absorption, optical absorption coefficient, extinction coefficient, and band gap energy determinations are conducted to investigate electromagnetic wave absorption capability of the nanocomposites. Resistivity measurement is studied as well. Electrical conductivity of the PVA is significantly increased with at least an improvement of 3000 times as compared to pure PVA (1 × 10−13 Sm−1). The highest σ value of 7.25 × 10−3 Sm−1 is found in the nanocomposites with a mass ratio of PVA to MXenes, 80:20 with its calculated optical absorption coefficient value in range 4000–5000 cm−1. The optical findings, as well as the electrical conductivity enhancement exhibited by these nanocomposites, explore the route to apply MXenes in polymer-based multifunctional nanocomposites for various applications such as optoelectronics, conductive filler, and electromagnetic absorbers.